PBP-2 Negative Methicillin Resistant Staphylococcus schleiferi Bacteremia from a Prostate Abscess: An Unusual Occurrence - Chandni Merchant; Daphne-Dominique Villanueva; Ishan Lalani; Margaret Eng; Yong Kang (Case Reports in Infectious Diseases)
Staphylococcus schleiferi subsp. schleiferi is a coagulase-negative Staphylococcus which has been described as a pathogen responsible for various nosocomial infections including bacteremia, brain abscess, and infection of intravenous pacemakers. Recently, such bacteria have been described to be found typically on skin and mucosal surfaces. It is also believed to be a part of the preaxillary human flora and more frequently found in men. It is very similar in its pathogenicity with Staphylococcus aureus group and expresses a fibronectin binding protein. Literature on this pathogen reveals that it commonly causes otitis among dogs because of its location in the auditory meatus of canines. Also, it has strong association with pyoderma in dogs. The prime concern with this organism is the antibiotic resistance and relapse even after appropriate treatment. Very rarely, if any, cases have been reported about prostatic abscess (PA) with this microbe. Our patient had a history of recurrent UTIs and subsequent PA resulting in S. schleiferi bacteremia in contrast to gram negative bacteremia commonly associated with UTI. This organism was found to be resistant to methicillin, in spite of being negative for PBP2, which is a rare phenomenon and needs further studies.